High performance liquid chromatography assessment of antibiotic residues in poultry and fish feeds in Bangladesh - Islam, Rafiza; Ahammad, Raju; Islam, Md. Mazharul; Shoeb, Mohammad; Mamun, Md. Iqbal Rouf (Current Research on Biosciences and Biotechnology, 2024)
The extensive use of antibiotics in animal feed in Bangladesh raises concerns in commercial poultry and fish feeds, posing risks of antibiotic resistance in the food chain. This study aimed to critically examine feed safety and quality by assessing tetracyclines (oxytetracycline, tetracycline, and chlortetracycline) and amoxicillin in commercially produced poultry and fish feeds. Fifteen feed samples from different areas in Dhaka and Gazipur were collected and subjected to extraction and analysis with a high-performance liquid chromatography (HPLC) with photodiode array detection (PDA) method. The HPLC method was validated for linearity (R2>0.999), accuracy, and precision, limit of detection or LOD (0.72 to 1.77 µgkg-1) and limit of quantification or LOQ (1.77 to 3.69 µgkg-1), meeting European Union and Codex Alimentarius Commission standards. Matrix-matched calibration curves for each antibiotic in poultry and fish feeds exhibited excellent linearity. The sensitivity of the HPLC system was demonstrated through low LOD and LOQ. Results indicated moisture content 6.58-11.22% in poultry feeds and 6.58-11.02% in fish feeds, while ash content 4.42-12.83% in poultry feeds and 4.94-8.23% in fish feeds. Antibiotics were found to be below detection limits in all feed samples, suggesting their absence or levels below the maximum residue limits established by regulatory bodies. The study highlights the importance of monitoring antibiotics in feed to ensure food safety and mitigate antibiotic resistance risks. Further research on a larger scale is recommended to validate these findings and contribute to the development of robust regulatory frameworks for antibiotic use in animal feed production in Bangladesh.